2004
DOI: 10.1016/j.rapm.2004.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Addition of dexmedetomidine prolongs duration of vasodilation induced by sympathetic block with mepivacaine in dogs

Abstract: The addition of dexmedetomidine prolongs the duration of vasodilation induced by stellate ganglion block with mepivacaine used for sympathetic block in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…sympathetic block) when combined with mepivacaine for stellate ganglionic blockade (Kimura et al. 2001; Tezuka et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sympathetic block) when combined with mepivacaine for stellate ganglionic blockade (Kimura et al. 2001; Tezuka et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two canine studies have demonstrated that both clonidine and dexmedetomidine will prolong the duration of vasodilation (i.e. sympathetic block) when combined with mepivacaine for stellate ganglionic blockade (Kimura et al 2001;Tezuka et al 2004). Clonidine's mechanism of analgesic action in this setting remains controversial with at least one clinical study suggesting that the effects are mediated centrally and not locally at the level of the nerve axon (Mannion et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their local and central analgesic characteristics, alpha-2 receptor agonists like clonidine have been employed as local anesthetic adjuncts for peripheral or central neuraxial blocks [ 3 ]. Dexmedetomidine is an alpha-2 agonist with eight times more affinity for alpha-2 receptors than clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic blocks (stellate ganglion block and lumbar plexus block) have been beneficial in patients with CRPS [ 2 ]. Alpha-2 receptor agonists such as clonidine and dexmedetomidine have been clinically used for central and peripheral nerve blocks because of their local and central analgesic effects [ 3 ].…”
Section: Introductionmentioning
confidence: 99%